Arterial Stiffness in Breast Cancer Patients Treated with Anthracycline and Trastuzumab-Based Regimens - Özlem Yersal; Ufuk Eryilmaz; Hakan Akdam; Nezih Meydan; Sabri Barutca (Cardiology Research and Practice)
Aims. Cardiovascular diseases are the primary cause of premature morbidity and mortality in early breast cancer patients after treatment with cardiotoxic chemotherapeutic agents. Arterial stiffness is an independent risk factor for future cardiovascular diseases and can be used as a predictive marker of subclinical cardiac damage. The aim of this study is to analyze the arterial stiffness in breast cancer patients who are in the follow-up period after receiving anthracycline-based chemotherapy regimens with trastuzumab. Methods and Material. We enrolled 45 HER2-positive breast cancer patients who are on follow-up at least for six months after completion of adjuvant chemotherapy with trastuzumab, and cardiovascular risk matched 30 control volunteers. The measurements were done with pulse wave analyzing machine. Results. Mean pulse wave velocity was higher in breast cancer patients compared to controls. The pulse wave velocity was significantly higher in patients receiving aromatase inhibitors compared to patients under tamoxifen. It was also significantly higher in postmenopausal breast cancer patients than postmenopausal controls. Conclusions. Arterial stiffness measurements may predict the breast cancer survivors with higher risk for cardiovascular events earlier in the follow-up period, and necessary preventive approaches and/or treatments can be applied.